Characterization of the Phospholipid Platelet-Activating Factor As a Mediator of Inflammation in Chickens - Garrido, Damien; Chanteloup, Nathalie K.; Trotereau, Angélina; Lion, Adrien; Bailleul, Geoffrey; Esnault, Evelyne; Trapp, Sascha; Quéré, Pascale; Schouler, Catherine; Guabiraba, Rodrigo (Frontiers in Veterinary Science, 2017)
Lipid mediators are known to play important roles in the onset and resolution phases of the inflammatory response in mammals. The phospholipid platelet activating factor (PAF) is a pro-inflammatory lipid mediator which participates in vascular- and innate immunity-associated processes by increasing vascular permeability, facilitating leukocyte adhesion to the endothelium and by contributing to phagocyte activation. PAF exerts its function upon binding to its specific receptor, PAFR, which is abundantly expressed in leukocytes and endothelial cells. In chickens, lipid mediators and their functions are still poorly characterized and the role of PAF as an inflammatory mediator has not yet been investigated. In the present study we demonstrate that primary chicken macrophages express PAFR and lysophosphatidylcholine acyltransferase 2 (LPCAT2), the latter being essential to PAF biosynthesis during inflammation. Also, exogenous PAF treatment induces intracellular calcium increase, ROS release and increased phagocytosis by primary chicken macrophages in a PAFR-dependent manner. We also show that PAF contributes to the E. coli LPS-induced pro-inflammatory response and boosts the macrophage response to E. coli LPS via PI3K/Akt- and CaMK II-mediated intracellular signaling pathways. Exogenous PAF treatment also increases avian pathogenic E. coli (APEC) intracellular killing by chicken macrophages, and PAFR and LPCAT2 are upregulated in chicken lungs and liver during experimental pulmonary colibacillosis. Finally, exogenous PAF treatment increases cell permeability and upregulates the expression of genes coding for proteins involved in leukocyte adhesion to the endothelium in primary chicken endothelial cells (chAEC). In addition to these vascular phenomena, PAF boosts the chAEC inflammatory response to bacteria-associated molecular patterns in a PAFR-dependent manner. In conclusion, we identified PAF as an inflammation amplifier in chicken macrophages and endothelial cells, which suggests that PAF could play important roles in the endothelium-innate immunity interface in birds during major bacterial infectious diseases such as colibacillosis.